2014
DOI: 10.1007/s00381-014-2479-3
|View full text |Cite
|
Sign up to set email alerts
|

Spinal epidural abscess from group A Streptococcus after varicella infection: a case report and review of the literature

Abstract: This is the third case of SEA from GAS reported in the literature in a pediatric population with varicella infection. We discuss here the clinical presentation and the diagnostic challenges for SEA in childhood through a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Also, in our case study, the CSF examination yielded pleocytosis, hypoglycorrhachia and elevated protein, but the CSF culture was sterile and polymerase chain reaction tests for common bacterial causes of meningitis were negative. It should be noted that lumbar punctures should not typically be performed in cases of suspected or confirmed SEA, as the procedure may result in further seeding of the infection .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, in our case study, the CSF examination yielded pleocytosis, hypoglycorrhachia and elevated protein, but the CSF culture was sterile and polymerase chain reaction tests for common bacterial causes of meningitis were negative. It should be noted that lumbar punctures should not typically be performed in cases of suspected or confirmed SEA, as the procedure may result in further seeding of the infection .…”
Section: Discussionmentioning
confidence: 99%
“…There are very few reports of paediatric SEA in the literature . Haematogenous spread from an intercurrent febrile illness, such as tonsillitis, pharyngitis, pneumonia, acute otitis media, skin and soft tissue infections, is the favoured route of infection, especially in infants and young children .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SEA is an infection that forms in the space between the bones of the spine and the lining membrane of the spinal cord. [16] In this study, a thoracic SEA case was presented with a clearly different mechanism from that of cervical SEA. The esophagus is located in the septum.…”
Section: Discussionmentioning
confidence: 99%
“…27 Reports have suggested that varicella infection may increase the risk for spinal epidural abscesses due to secondary bacterial. [28][29][30] Infection with poliovirus, herpes virus, and cytomegalovirus (especially in patients with HIV) can also result in myelitis. With interruption of wild poliovirus circulation from many parts of the world, myelitis associated with it has decreased in the recent years.…”
Section: Introductionmentioning
confidence: 99%